The Impact of Bio-Based Fertilizer Integration Into Conventional Grassland Fertilization Programmes on Soil Bacterial, Fungal, and Nematode Communities - Ryan, Demi; Karpinska, Anna; Forrestal, Patrick J.; Ashekuzzaman, S. M.; Kakouli-Duarte, Thomais; Dowling, David N.; Germaine, Kieran J. (Frontiers in Sustainable Food Systems, 2022)
Phosphorus (P) is an essential plant macro-nutrient applied to soil in agriculture, mainly sourced from non-renewable mined phosphate-rock, of which readily accessible reserves are currently under pressure, while global food demand continues to grow. Meanwhile, an abundance of P is lost in waste-streams. Hence, bio-based fertilizers are increasingly produced using nutrient-recovery technologies and evaluated as a sustainable fertilizer alternative. However, there is little knowledge of how these products affect soil microorganisms. In this study, four new phosphate bio-based fertilizers (two struvite and two incinerator ashes) were assessed in permanent grassland-plots to understand their impact on soil bacterial, fungal, and nematode community responses. The experiment consisted of 40 plots (each 6 × 2 m2) of 8 treatments (2 struvite, 2 ash, cattle slurry, 100% mineral fertilizer, zero P fertilizer, and a control without fertilization) with 5 replications arranged in a randomized complete block design. Community data were obtained by amplicon sequencing of DNA extracted from soil samples and subsequent analysis of community composition, diversity, structure and influencing environmental variables. Diversity of the soil microorganisms was maintained by all bio-based fertilizer treatments. Results showed that soil bacterial, fungal, and nematode communities of the struvite-treatments were similar to those in 100% mineral treatment. Communities in ash-treatments were more disturbed in their compositions, abundances and structures, possibly due to their high pH and heavy metal content. From canonical correspondence analysis, available P, K, and Mg, as well as plant P uptake and biomass yield, were identified as factors significantly influencing bacterial and nematode communities across different treatment groups. In particular, the abundance of environmental disturbance sensitive nematodes (e.g., Dorylaimida) was significantly reduced by one of the ash products. Overall, results indicate that both struvites are benign to soil bacterial, fungal, and nematode communities and can be safely applied as a source of renewable P to meet crop nutrition requirement. The ash products require further investigations before recommending their regular application as fertilizer. As the application of novel bio-based fertilizers will increase in the foreseeable future, the findings of this study would be valuable to feed into developing environmental risk assessment protocols.